Relationship between clinical severity of respiratory syncytial virus infection and subtype. Issue 2 (August 1996) - Kneyber, M C; Brandenburg, A H; Rothbarth, P H; de Groot, R; Ott, A; van Steensel-Moll, H A
Abstract : The relationship between clinical severity of respiratory syncytial virus (RSV) infection and distribution of subtype A or B was investigated. The data of 232 children, who were admitted with RSV infection or diagnosed in the outpatient department of the Sophia Children's Hospital, Rotterdam between 1992 and 1995, were studied. The diagnosis of RSV was confirmed by a direct immunofluorescence assay. Subtyping was performed by an indirect immunofluorescence assay using specific monoclonal antibodies. Gender, age at diagnosis, gestational age and birth weight, the presence of underlying diseases, feeding difficulties, the presence of wheezing and retractions, respiratory rate, temperature, clinical diagnosis at presentation, oxygen saturation (SaO2), carbon dioxide tension (PCO2), and pH, characteristics of hospitalisation, and the need for mechanical ventilation were observed. Analysis was performed on data from all patients diagnosed with RSV infection in the period between 1992 and 1995 spanning three RSV seasons, and separately on the RSV season 1993-4. The outcome of the three year analysis (150 (64.7%) subtype A v 82 (35.3%) subtype B) was compared with the outcome of the season 1993-4, a mixed epidemic with 37 (60.7%) subtype A and 24 (39.3%) subtype B isolates. None of the variables observed in the season 1993-4 differed significantly between RSV subtype A and B. Similar results were obtained from the analysis in the period 1992 until 1995, with the exception of PCO2 (a higher PCO2 was found in subtype A, p < 0.001) and retractions (more retractions were noted in patients with subtype A, p = 0.03). After correcting for possible confounders using regression analysis, these differences were not significant anymore. The data indicate that there is no relationship between clinical severity of RSV infection and subtype.